2013
DOI: 10.1089/ped.2012.0182
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Wheezing in the Midst of Nutritional Transition: A Study in Brazil

Abstract: To assess the influence of dietary patterns on the prevalence of wheezing in the child and adolescent population in Northeastern Brazil. This is a cross-sectional study of male and female students, 6-12 years old, from the public elementary schools of Sã o Francisco do Conde, Bahia, Northeastern Brazil. The report of wheezing in the past 12 months was collected using a questionnaire from the International Study of Asthma and Allergies in Childhood Program phase III, adapted to Portuguese. Consumption patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Many of the methodologies and instruments developed for the SCAALA studies are being used in the ECUAVIDA cohort, and hypotheses generated by these studies are being tested in the ECUAVIDA cohort in a prospective manner using a wider range and/or more refined set of instruments. 45 , 48 , 49 …”
Section: What Has It Found?mentioning
confidence: 99%
“…Many of the methodologies and instruments developed for the SCAALA studies are being used in the ECUAVIDA cohort, and hypotheses generated by these studies are being tested in the ECUAVIDA cohort in a prospective manner using a wider range and/or more refined set of instruments. 45 , 48 , 49 …”
Section: What Has It Found?mentioning
confidence: 99%
“…There are reports that a high proportion of asthma cases in Latin America are not attributable exclusively to atopy 25 . Many factors have been proposed to explain the high prevalence of nonatopic asthma, including home humidity and respiratory infections in childhood 26 , aspects that indicate poverty (such as low maternal schooling and filth in the household) 27 and, more generally, low socioeconomic conditions 28 , nutritional 29,30 and psychosocial aspects 31,32 . Certainly, the identification of the most relevant risk factors will be crucial to subsidize the development of interventions that aim at the prevention and control of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Clemmer et al [ 31 ] used PCA to demonstrate that a clinical ‘endophenotype’ relating to corticosteroid responsiveness best predicted corticosteroid response in all replication populations. Other studies in Brazilian [ 26 ], British [ 28 ], and Japanese [ 41 ] children have shown that ‘Western diets’ were independently associated with an increased risk of wheezing by school age.…”
Section: Clustering Methods In Asthma Subtypingmentioning
confidence: 99%